(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Computed Tomography (CT) scans are indispensable in modern diagnostic imaging but are associated with significant radiation exposure. Optimizing CT protocols is essential to balance image quality with radiation dose reduction. This paper reviews key strategies for protocol optimization, including tube current modulation, iterative reconstruction algorithms, kVp adjustment, and advanced post-processing techniques. We present comparative data from clinical studies demonstrating how optimized protocols maintain diagnostic accuracy while lowering patient dose.